1948
DOI: 10.1103/physrev.74.1046
|View full text |Cite
|
Sign up to set email alerts
|

On Nuclear Dipole Vibrations

Abstract: The high frequency resonances recently observed for (y,n) reactions as well as photo-fission are interpreted in analogy with the "reststrahl frequencies" of polar crystals. The estimated frequencies are in good agreement with the experimental results. An interesting consequence of this interpretation is the conclusion that strong resonance scattering of 7-rays should take place at a frequency characteristic of the scattering nucleus. I T has been observed recently 1 that some nuclear photo-disintegrations, (y.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
297
1
10

Year Published

1968
1968
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 652 publications
(316 citation statements)
references
References 8 publications
(3 reference statements)
8
297
1
10
Order By: Relevance
“…This means that the PLS charge center can be shifted from the PLS center-of-mass. A similar process of a dipole charge polarization is well known in electromagnetic interactions with nuclei as a Goldhaber-Teller and Steinwedel-Jensen giant resonances [10,11]. Since the evaporation rate is very fast at high excitation energies, the charge distribution of the evaporated particle and the residue should correspond to this 'dipole' shift of the PLS charge distribution.…”
Section: Theoretical Interpretationmentioning
confidence: 74%
“…This means that the PLS charge center can be shifted from the PLS center-of-mass. A similar process of a dipole charge polarization is well known in electromagnetic interactions with nuclei as a Goldhaber-Teller and Steinwedel-Jensen giant resonances [10,11]. Since the evaporation rate is very fast at high excitation energies, the charge distribution of the evaporated particle and the residue should correspond to this 'dipole' shift of the PLS charge distribution.…”
Section: Theoretical Interpretationmentioning
confidence: 74%
“…In a macroscopic approach, the isovector GDR is interpreted by a combination of the Steinwedel-Jensen model in which the total density is kept unchanged [51] and the Goldhaber-Teller model where proton and neutron fluids are incompressible [4]. It is obvious that the Steinwedel-Jensen model does not affect the quadrupole moment because any modification of the density of one isospin specie is exactly compensated by the other in every point of space.…”
Section: Evolution Of the Coupling With Isospin And Massmentioning
confidence: 99%
“…At this beam energy the monopole-dipole excitation is of order of 1 barn. The total cross section contains an interference between the amplitudes a (1) f i and a (2) f i . This is shown in Table 2 for 100A MeV for which the effect is larger.…”
Section: Excitation By a Deformed Nucleusmentioning
confidence: 99%
“…However, in Ref. [42] the source for anharmonic effects were discussed and it was suggested that it should be very small, i.e., ∆ (2) …”
Section: Effect Of Resonance Widthsmentioning
confidence: 99%
See 1 more Smart Citation